The strategy for implementing National Fish Logistics System (NFLS) in Bitung Fishing Port, Bitung, Indonesia - Tassi, Maltonius; Kepel, Rene Charles; Sinjal, Hengk (AQUATIC SCIENCE & MANAGEMENT, 2017)
Title (Bahasa Indonesia): Strategi implementasi Sistem Logistik Ikan Nasional (SLIN) di Pelabuhan Perikanan Samudera Bitung, Bitung, Indonesia Regulation of the Minister of Marine and Fisheries of Indonesia 2014 (No.5/MEN/2014) regarding National FishLogistics System (NFLS) is a policy issued in order to overcome the problem of limited raw materials of fish. In order to implement the regulation optimally at Bitung Fishing Port (BFP), this study was carried out which aimed to predict production of capture fisheries landed in BOFP for the next 10 years, to identify external and internal factors in formulating alternative strategies, and to set up priorities strategy for NFLS implementation at the BOFP. This descriptive study was carried out using several analyses, namelySimple Regression Analysis, SWOT (Strengths, Weakness, Opportunities, and Threats), and Quantitative Strategic Planning Matrix (QSPM). The result of the study showed that the increase in production canstilloccurin accordance with the projections of the secondary data overthe past10 years. The internal factors that become a strength in the implementation of NFLS was the vision of BOFP to increase landings of fishery catch (score 0.660). The weakness was existence of the storehouse of fish which still limited (score 0.440). The external factors seen as opportunities of NLSF implementation was the location of potential fishing ground (score 0,495), while the threats was the cost of fishing operations which are relatively expensive (score 0.440). This study also formulatedsix alternative strategies that can be applied in the implementation of NLSF at BOFP and the best strategies are the optimization of the fleet, loading and unloadingfacilities, and logisticschanneling facilities  in fishing ground with the potential to increase fisheries production (TAS = 5,544).Peraturan Menteri Kelautan dan Perikanan 2014 (No.5/MEN/2014)tentang sistem logistikikan nasional (SLIN) merupakan kebijakan dalam upayamengatasi masalah keterbatasan bahan baku ikan. Untuk mengimplementasikan peraturan tersebut secara optimal di Pelabuhan Perikanan Samudera Bitung (PPSB), maka penelitian ini dilakukan di mana bertujuan untukmemprediksi produksi perikanan tangkap yang didaratkan di PPSBuntuk 10 tahun yang akan datang, mengidentifikasi faktor eksternal dan internaldalam merumuskan strategialternatif, dan menetapkan prioritas strategi implementasi SLIN. Penelitianini merupakan penelitian deskriptifmenggunakan beberapaanalisis, yaituanalisis Regresi Sederhana,SWOT (Strengths,Weakness,Opportunity,Thread),dan Quantitative Strategic Planning Matriks(QSPM).Hasil penelitian menunjukan,bahwa peningkatan produksi masih dapat terjadi sesuai dengan proyeksi data sekunder selama 10 tahun terakhir. Faktor internal yang menjadi kekuatan dalam implementasi SLINialah adanya visi PPSB untuk meningkatkan pendaratan hasil perikanan tangkap (skor 0,660).Sedangkan kelemahannya ialahkeberadaan gudang penyimpanan ikan yang masih terbatas (skor 0,440). Faktor eksternal yang menjadi peluang dalam implementasi SLIN ialahlokasi daerah penangkapan ikan yang potensial (skor 0,495).Sedangkan ancamannya ialah biaya operasi penangkapan ikan yang relatif mahal (skor 0,440). Penelitian ini juga merumuskan enam alternatif strategi yang dapat diterapkan dalam implementasi SLIN di PPSBdi mana strategi terbaiknyaialahoptimasi armada, sarana bongkar muat, dan sarana penyalur logistik pada daerah penangkapan ikan yang potensial untuk meningkatkan produksi perikanan tangkap (TAS = 5,544).